From Photophobia to Achromatopsia. How to Establish the Correct Diagnosis - M. F. Shurygina; A. M. Khoteeva; I. A. Mishina; V. A. Pismenskaya (Oftalʹmologiâ)
Achromatopsia is a congenital autosomal recessive disorder characterized by decreased or absent cone’s function. Clinical symptoms include photophobia, nystagmus, low best corrected visual acuity, complete or incomplete color vision. Mutations in the CNGA3 and CNGB3 genes are responsible for approximately 70–80 % of all achromatopsia cases. The purpose: to evaluate the results of a comprehensive clinical and genetic examinations of four patients with an established diagnosis of achromatopsia. Onset of the disease in all patients was in the form of severe photophobia and nystagmus, appearing at the age from 1.5 to 11 months. According to optical coherence tomography exams were detected structural changes in neuroepithelium (three patients), varied from subfoveal disorganization of the photoreceptor outer segments with “blurring” of the external limiting membrane line and ellipsoid zone to subfoveal destruction of the photoreceptor outer segments and the presence of a slit defect. Out of seven identified mutations in the CNGA3 and CNGB3 genes, two were previously detected in Russian patients, and five were not detected in the Russian Federation.